Expression Profiling and Functional Implications of a Set of Zinc Finger Proteins, ZNF423, ZNF470, ZNF521, and ZNF780B, in Primary Osteoarthritic Articular Chondrocytes - Maria Mesuraca; Olimpio Galasso; Leonardo Guido; Emanuela Chiarella; Stefania Scicchitano; Renaud Vatrinet; Giovanni Morrone; Heather M. Bond; Giorgio Gasparini (Mediators of Inflammation)
Articular chondrocytes are responsible for the maintenance of healthy articulations; indeed, dysregulation of their functions, including the production of matrix proteins and matrix-remodeling proteases, may result in fraying of the tissue and development of osteoarthritis (OA). To explore transcriptional mechanisms that contribute to the regulation of chondrocyte homeostasis and may be implicated in OA development, we compared the gene expression profile of a set of zinc finger proteins potentially linked to the control of chondrocyte differentiation and/or functions (ZNF423, ZNF470, ZNF521, and ZNF780B) in chondrocytes from patients affected by OA and from subjects not affected by OA. This analysis highlighted a significantly lower expression of the transcript encoding ZNF423 in chondrocytes from OA, particularly in elderly patients. Interestingly, this decrease was mirrored by the similarly reduced expression of PPARγ, a known target of ZNF423 with anti-inflammatory and chondroprotective properties. The ZNF521 mRNA instead was abundant in all primary chondrocytes studied; the RNAi-mediated silencing of this gene significantly altered the COL2A/COL1 expression ratio, associated with the maintenance of the differentiated phenotype, in chondrocytes cultivated in alginate beads. These results suggest a role for ZNF423 and ZNF521 in the regulation of chondrocyte homeostasis and warrant further investigations to elucidate their mechanism of action.